Archaeological supervision in the Monastery of St. Francis in Zadar (In situ, 2024)
In the period from May to September 2022, during remodeling and renovation of the western building of the Monastery of St. Francis in Zadar, the Department of Archeology carried out archaeological supervision over all earthworks carried out as part of the renovation. Earthworks as part of the renovation were mainly related to excavations of foundations so that they could be documented and reinforced. The width of the trench was usually up to 100 cm, and the depth depended on the depth of the foundations. Excavations inside the western part of the monastery complex suggest that the biggest changes took place during the Baroque period in the 18th century. Postmedieval tombs with multiple burials and a layer of dislocated bones among them were found during the excavations inside the cloister, as expected.
Keywords: archaeological supervision; Monastery of St. Francis; Zadar; Medieval period; Modern era